Evaluation of IT-Based SCM System Using the DeLone and McLean Model - Kurnia Sastradipraja, Cecep; Zulkifli, Ridwan; Lestari Utami, Lita; Anisah Puspowati Harori, Rr. Isni; Syarifudin, Herry (Jurnal Sistem dan Informatika (JSI), 2025)
This qualitative case study evaluates the effectiveness of the IT-based Supply Chain Management (SCM) information system developed at PT Hifni Jaya Makmur (PT HJM), a medium-scale agricultural commodity company specializing in coffee and black pepper. The company faces challenges, including seasonal fluctuations in raw material supply and limited vehicle availability for deliveries. To address these issues, a digital SCM system was implemented, featuring key features such as demand forecasting using the Single Exponential Smoothing (SES) method, safety stock calculation, and delivery monitoring. The evaluation was conducted using the DeLone and McLean Information System Success Model, which involves six dimensions: system quality, information quality, service quality, usage, user satisfaction, and net benefits. Data were collected through triangulation of interviews, observations, and system documentation. Findings indicate that the system significantly improved procurement accuracy, reduced processing time, and enhanced delivery planning. However, further enhancements such as multi-period forecasting, automated vehicle scheduling, and integration with external data sources are recommended to increase the system's effectiveness.